The Perspective of Dienul-Islam in Reviewing Leadership for People - Abdullah, Mulyana; Wilodati, Wilodati; Abdulhakam, Kama; Fitria, Ratna (Universitas Pendidikan Indonesia (UPI), 2021)
Raising leader is a must at the same time as the demand for muslims. The problem is what are the policies and the act of us as the muslims whose stay and live in a country which it’s not an Islamic state like Indonesia in the case of choosing the leader? Trough the implementing literacy and documentation study to a view of literature and report, this study found that The differences opinion among the clergies seen the one hand emphasized that the charge of muslim is forbidden being raised from among non-muslim. It is also the same with the other who insisted that raised the leader of the people from non-muslims it is permitted. In addressing these difference oppinions, the muslims who stay and live in Indonesia as a country with plural communities, should getting wiser to choose. The thing that most important to be understood is based on welfare for all citizens, there are some common law of syara’.